A CRITICAL STUDY OF THE LORE OF LORD BUDDHA IN AŚVAGHOṢA’S - Das, Pitas (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A Buddhist monk of the first or second century C.E., Aśvaghoṣa comprised a Buddha-Carita poem consisting of fourteen cantos. He maybe belonged to Ayodhya, a place in North Central India. His work Buddha-Carita or ‘Life of Buddha’ takes the readers from the birth of Siddhartha to his development. Aśvaghoṣa’s main aim was not to amuse but to teach to present the Buddha’s teaching as the climax of the Brahmanical tradition. His Buddha-Carita is a response to Brahmanical challenges where we can notice two major points. First, he presents the Buddha’s doctrine the dharma discovered through his development as the consummation of the Brahmanical religion, a preparation for the appearance of Buddha. Brahmanism is the expectation of Buddha and Buddhism is the satisfaction of Brahmanism. So, it is incorrect to see both as contradictory or opposing theories. The present paper is an attempt to focus on how Aśvaghoṣa presents the context and significance of the lore of Lord Buddha.